The Transition to Modern Awards: Challenges for Small and Medium Enterprises in Western Australia - Aitken-Fox, Eileen (2017)
Statistics gathered by the Department for Business Innovation and Skills (UK) in 2015 show that total employment in small and medium enterprises (SMEs) was 15.6 million, representing 60% of private sector employment in the United Kingdom. Similarly, SMEs in Australia are significant employers and this is reflected in the State of Western Australia (WA) where SMEs account for over 99% of employing businesses. While there is limited existing research into industrial relations compliance in SMEs, United Kingdom studies by Anderson and Ullah (2014), Harris (2002), Schmidt and colleagues (2007), and Ullah and Smith (2015) found that SMEs are challenged by the complexity of industrial legislation, are time poor, and balance time spent on compliance with business survival. These findings were supported by research into small business experience with regulations undertaken by the Australian Government Productivity Commission (2013). This latter research also found that small business owners are time poor, have limited time to read regulations, need help interpreting regulations, and that support material provided by Government needs to be simplified.